Amine Salts Vapor Healing Perfected Perovskite Layers for NiOx Based p‐i‐n Solar Cells. (5th August 2022) - Li, Yu; Lin, Zedong; Wang, Jian; Xu, Rongguo; Zhang, Kai; Wang, Gaopeng; Liu, Tongfa; Zhou, Huanping; Xiao, Shuang; Yang, Shihe
Abstract: Post‐treatment is a widely used strategy to reduce defects in perovskite films, but has been largely limited to the solution phase. Herein, the posttreatment tool kit and develop a universal amine salts (A I X I ) vapor healing strategy by taking advantage of the penetrating power of vapor and the soft‐matter characteristics of halide perovskite is expanded. In a striking demonstration, the post‐treatment of pristine perovskite layers allows simultaneous filling of the MA + and I – vacancies, passivation of both the cation and anion defects, and healing of the films to high order and high crystallinity required for high device performance, from the surface to the bulk and all the way down to the bottom. Experiments and DFT calculations revealed that charge extraction can be enhanced and non‐radiative recombination can be reduced by regulating the energy levels and reducing the trap states via the A I X I vapor healing. Moreover, the diffusing A I X I can reach the NiOx surface to obstruct the undesirable interfacial reactions and passivate the interface defects, further reducing the open‐circuit voltage ( V oc ) loss. The vapor healing strategy substantially reduces the trap density from 4.76 × 10 15 to 1.04 × 10 15 cm –3, and promots power conversion efficiency of the champion device from 17.92% to 20.48% with superior device consistency, V oc up to 1.114 V and the operational device stability. Abstract : An amine salts vapor healing strategy is applied to simultaneously passivate the defects across the entire perovskite film and obstruct the interfacial redox reaction between NiOx and perovskite, enhancing both the device performance and the performance consistency. The vapor healing strategy substantially reduces the trap density and promotes device power conversion efficiency from 17.92% to 20.48% with improved operational device stability.